Infrared Thermogram Temperature Trends of Body Extremities of Tharparkar and Karan Fries Cattle during the Extreme Climatic Conditions - Muhammed N.V., Afreed; Vir Singh, Sohan; Bhalakiya, Nikita; Ukey, Apeksha; Kumar , Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
In order to compare the surface temperature of body extremities of Tharparkar and Karan Fries cattle under extreme climatic conditions during summer and winter season, the present study was carried out under standard managemental conditions. Environmental parameters, including temperature and humidity, were recorded daily, and Temperature Humidity Index (THI) and Black Globe Humidity Index (BGHI) were calculated to assess the level of thermal comfort on cattle. Thermal imaging (Infradred thermography, IRT) of body extremities (muzzle, nose bridge, ear tip and base, fetlock, and knee) were recorded twice weekly during winter (Dec. 2022–Jan. 2023), spring (Feb.–March 2023), and summer (June–July 2023) season. Skin extremities temperature was highest during summer followed by spring and winter season in both the breeds of cattle. Significant (p